Artificial Intelligence in Oral Health - Lee, Jae-Hong (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue is intended to lay the foundation of AI applications focusing on oral health, including general dentistry, periodontology, implantology, oral surgery, oral radiology, orthodontics, and prosthodontics, among others.